Impact of rotavirus vaccination on diarrheal disease burden of children in South America - Tanmoy Bose; Ray Borrow; Peter D Arkwright (Expert Review of Vaccines, 2024)
Introduction Rotavirus is a leading cause of severe diarrheal disease and death in children under five years of age worldwide. Vaccination is one of the most important public health interventions to reduce this significant burden.Areas covered This literature review examined vaccination coverage, hospitalization rate, mortality, genotypic distribution, immunogenicity, cost-effectiveness, and risk versus benefit of rotavirus vaccination in children in South America. Nine out of twelve countries in South America currently include a rotavirus vaccine in their national immunization program with coverage rates in 2022 above 90%.Expert opinion Introduction of the rotavirus vaccination has led to a marked reduction in hospitalizations and deaths from diarrheal diseases in children under 5 years, particularly infants under 1 year, in several South American countries. In Brazil, hospitalizations decreased by 59% and deaths by 21% (30–38% in infants). In Peru, hospitalizations in infants fell by 46% and deaths by 37% (56% in infants). Overall, data suggest that rotavirus vaccination has reduced rotavirus deaths by 15–50% in various South American countries. There is some evidence that immunity wanes after the age of 1-year old. Ongoing surveillance of vaccine coverage and changes in morbidity and mortality is important to maximize protection against this disease.